Orthopedic injuries in a tertiary hospital: an epidemiological and economic analysis of the implants used - Igor Fiorese Vieira; José Luiz Lopes Vieira; Luciana Ferreira; Eric Schmiseila; Anitta Bittar e Silva; Mateus Strazzi Barreto; Sergio Skrobot (Universidade Estadual de Maringá, 2024)
Identifying the cost and prevalence of orthopedic implants used to fix complex fractures.  This is a retrospective study whose data analysis was carried out via a digital database from a tertiary trauma hospital in southern Brazil. A total of 481 fractures from 397 patients were included. In total, 479 orthopedic implants were used. Most patients were male (90.65%; n 364) with a mean age of 42.7 years. The lower limbs predominated in the sample with 90.44% prevalence (N = 435). The Ilizarov device was the most used implant (N = 61), mainly in fractures of the tibia diaphyseal region (N = 30), which was the most fractured bone region (N = 105). Considering this specific segment, the universal nail (N = 42) was the most used implant. The Ilizarov device showed the highest cost regarding the implants (6.33 times more expensive than the 3.5mm DCP implant - reference), whereas the femoral nail had an index of 6.09 and the tibial nail of 5.96. The use of conventional materials, that is, the ones with 4.5mm or 3.5mm, proved to be less expensive, however, less used in face of any orthopedic injury. The Ilizarov-type external fixator was the most expensive and most widely used device in the setting of complex orthopedic injuries.